Tau enhances α-synuclein aggregation and toxicity in cellular models of synucleinopathy. - Nahuai Badiola (Public Library of Science (PLoS), 2011)
Background The simultaneous accumulation of different misfolded proteins in the central nervous system is a common feature in many neurodegenerative diseases. In most cases, co-occurrence of abnormal deposited proteins is observed in different brain regions and cell populations, but, in some instances, the proteins can be found in the same cellular aggregates. Co-occurrence of tau and α-synuclein (α-syn) aggregates has been described in neurodegenerative disorders with primary deposition of α-syn, such as Parkinson's disease and dementia with Lewy bodies. Although it is known that tau and α-syn have pathological synergistic effects on their mutual fibrillization, the underlying biological effects remain unclear. Methodology/principal findings We used different cell models of synucleinopathy to investigate the effects of tau on α-syn aggregation. Using confocal microscopy and FRET-based techniques we observed that tau colocalized and interacted with α-syn aggregates. We also found that tau overexpression changed the pattern of α-syn aggregation, reducing the size and increasing the number of aggregates. This shift was accompanied by an increase in the levels of insoluble α-syn. Furthermore, co-transfection of tau increased secreted α-syn and cytotoxicity. Conclusions/significance Our data suggest that tau enhances α-syn aggregation and toxicity and disrupts α-syn inclusion formation. This pathological synergistic effect between tau and α-syn may amplify the deleterious process and spread the damage in neurodegenerative diseases that show co-occurrence of both pathologies.